1997
DOI: 10.1046/j.1471-4159.1997.68031209.x
|View full text |Cite
|
Sign up to set email alerts
|

Glial Alkalinization Detected In Vivo by 1H‐15N Heteronuclear Multiple‐Quantum Coherence‐Transfer NMR in Severely Hyperammonemic Rat

Abstract: glutamine amide protons were selectively observed in vivo by 1H-15N heteronuclear multiple-quantum coherence-transfer NMR in spontaneously breathing, severely hyperammonemic rats during intravenous [15N]ammonium acetate infusion and the subsequent recovery period. The Iinewidth of brain [5-15N]glutamine amide proton H~increased from 36 ± 2 Hz at 3.4 h to 58 ±6 Hz after 5.7 h of infusion, a net increase of 22 ± 6 Hz. Concomitantly, brain ammonia concentration increased from 1.7 to 3.5 ± 0.2~tmol/gand the rat pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Two-thirds of the increase was attributed to ammonia-induced intracellular alkalinization which promotes GLU transport because it is driven by cotransport of one H + and three Na + ions in exchange for one K + . Our previous study (Kanamori and Ross 1997) showed that glial alkalinization in rat brain in vivo, as observed by NMR, occurred only under severe hyperammonemia when blood and brain NH 3 concentration exceeded 1.3 lmol/g and 3 lmol/g, respectively; no change in glial pH occurred at blood and brain NH 3 concentration of 0.9 lmol/g and <1.9 lmol/g, respectively, i.e. at concentrations observed in this study.…”
Section: Effect Of Hyperammonemia On Glu Transportsupporting
confidence: 64%
“…Two-thirds of the increase was attributed to ammonia-induced intracellular alkalinization which promotes GLU transport because it is driven by cotransport of one H + and three Na + ions in exchange for one K + . Our previous study (Kanamori and Ross 1997) showed that glial alkalinization in rat brain in vivo, as observed by NMR, occurred only under severe hyperammonemia when blood and brain NH 3 concentration exceeded 1.3 lmol/g and 3 lmol/g, respectively; no change in glial pH occurred at blood and brain NH 3 concentration of 0.9 lmol/g and <1.9 lmol/g, respectively, i.e. at concentrations observed in this study.…”
Section: Effect Of Hyperammonemia On Glu Transportsupporting
confidence: 64%
“…In contrast, an increase in the pH i by 0.3-0.4 units was observed in vivo by 1 H-15 N HMQC measurements on hyperammonemic rats. [33]. Portacaval anastomosis increases astrocytic pH i in rat brains, which may be a necessary concomitant of cellular volume regulatory processes [34].…”
Section: Discussionmentioning
confidence: 99%
“…One major disadvantage of the technique that NMR spectroscopists have to fight with, its low sensitivity because of the small energies involved, has turned out to be a major advantage for its application in the biomedical field: the low energy of the radiation in the radio frequency range that is used in NMR spectroscopy does not lead to significant tissue damage in living objects. This characteristic has been the basis for the development of fields such as magnetic resonance imaging providing information about entire organs as well as in vivo NMR spectroscopy which focuses on the investigation of small molecules in living systems ranging from suspensions of bacterial solutions to entire perfused organs [1][2][3][4][5][6]. In vivo NMR spectroscopy has provided a wealth of information about the distribution and metabolic turn over rates of sugars, amino acids as well as other molecules.…”
Section: Introductionmentioning
confidence: 99%